Filsafat Politik Perspektif Qutb al-Din Al-Shirazi - Islamiyati, Rosi (Indonesian Journal of Islamic Theology and Philosophy, 2020)
When talking about politics, for some people assume that the most important thing is the vast area, the expansion of the region, a large mass, or even a long lasting power. However, there are other things that are more important than these things namely the ethical, economic and political dimensions. because if power alone is not supported by a good economy, ethics and politics, then the State will still be a bad country and make its citizens will not live comfortably. Based on this consideration, this research is also present, this research will discuss how the political thinking of Qutb al-Din Al-Shirazi? This research uses descriptive analysis and interpretation methods. The results showed, As-Shirazi discussed political studies into three dimensions, namely ethics, economics and politics. It is interesting that As-Shirazi not only explained the three fields of study of practical philosophy separately. Instead, he concocted the three studies into one and interconnected. When talking about politics, of course it will not be separated from how the economy of a government runs. while politics and economics will not run straight when the ethical dimensions in both fields are underestimated. In fact, then ethics became the regulator and the wall of the two fields of study